Bazedoxifene for the prevention of postmenopausal osteoporosis - Luigi Gennari; Daniela Merlotti; Vincenzo De Paola; Giuseppe Martini; Ranuccio Nuti (Dove Medical Press, 2008)
Luigi Gennari, Daniela Merlotti, Vincenzo De Paola, Giuseppe Martini, Ranuccio NutiDepartment of Internal Medicine, Endocrine-Metabolic Sciences and Biochemistry, University of Siena, Policlinico Le Scotte 53100-Siena, ItalyAbstract: Bazedoxifene acetate is a novel, chemically distinct selective estrogen receptor modulator (SERM) that has been specifically developed after a stringent preclinical screening in order to obtain favorable effects on the skeleton and lipid metabolism with the additional improvement of a neutral effect on hot flushes and without stimulating the uterus or the breast. In both preclinical and clinical studies this SERM was shown to maintain BMD, prevent fractures, and reduce total cholesterol. Moreover, bazedoxifene also showed an improved uterine profile and demonstrated estrogen antagonistic activity on the endometrium. Importantly, this latter capacity has led to the development of a novel class of menopausal therapy called tissue selective estrogen complex (TSEC), in which bazedoxifene is combined with conjugated estrogen. The rationale for selecting bazedoxifene as the SERM in this TSEC combination is that it may offset estrogen stimulation of endometrial and breast tissue, without the necessity of using a progestin in women with an intact uterus, without aggravating menopausal vasomotor symptoms, but with an additive effect on bone. Preliminary data from phase 3 clinical trials appear to confirm this hypothesis, showing a greater effect of bazedoxifene on BMD with respect to raloxifene, coupled with efficacy on menopausal vasomotor symptoms not achieved by SERM alone. These properties and the safety profile of this combination, if confirmed long-term in ongoing phase 3 trials, might significantly affect the way women and physicians approach menopause and its related disorders.Keywords: bazedoxifene, SERM, estrogen, postmenopausal osteoporosis, treatment